A summary overview of the new, direct, target-specific oral anticoagulants - G. L. Muntingh (South African Family Practice)
In the past 10 years or so, many alternatives to warfarin have been developed the first being the novel oral anticoagulants (NOAC) or better referred to as direct oral anticoagulants (DOAC) or target-specific oral anticoagulants (TSOAC). These drugs have some definite advantages and disadvantages that should be clear to physicians before prescribing any of them for patients. Many clinical trials have provided definitive information about the efficacy and safety of DOACs, yet many physicians remain sceptical about prescribing these drugs due to lack of answers to real world questions. The concerns are directed towards appropriate patient selection (the choice should be made according to age, renal function, compliance, cost, clinical condition, intake of other drugs), the mechanism of switching between agents, how these drugs affect routine laboratory tests and when monitoring is needed. Knowledge of other drugs that interact with the DOAC and management of severe bleeding will be reviewed and recommendations will be given to all of these concerns.